The reliability of heart rate variability measurement performed by an immediately repeated test-retest procedure - Cipryan, L.; Litschmannova, M. (The biomedical basis of elite performance. 19-21 March 2012, London, UK. Abstracts & Manuscripts, 2012)
At present, analysis of heart rate variability (HRV) is becoming widely used as a clinical or research tool. Additionally, HRV analysis represents an interesting possibility for controlling and managing the sport training process. Supported reliability studies for HRV measurement are, however, still limited. The test-retest procedure is often used for HRV reliability evaluation with repeating the retest after several hours or days. Since HRV can be influenced by a number of internal or external factors, it is more appropriate, in our opinion, to repeat the retest immediately without any interruption (even if this procedure also has limitations). The main purpose of the present study was to perform an assessment of the absolute and relative reliability of standard indexes of HRV from short-term laboratory recordings by means of orthoclinostatic stimulation (supine . standing . supine). The study group consisted of 60 participants (mean age (min - max): 22 (19 . 26) years; males). The second measurement was repeated immediately after the first measurement under the same conditions. Standard HRV indexes were computed: PT (total spectral power), PHF (high frequency spectral power; absolute units), PLF (low frequency spectral power; absolute and normalized units) and LF/HF. According to Pinna et al. (2007), absolute reliability was assessed by 95 % limits of random variation; relative reliability was assessed by the intraclass correlation coefficient (ICC). There was also an estimate of the sample size needed to detect the mean difference . 30 % of the between-subject S.D. A significant mean change was only determined in the standing position in the parameters: PT, PHF, PLF. The second measurement was, in individual subject, as high/low as 1.27/0.82 times (LFnu, standing position, best case) and 5.88/0.15 times (LF/HF, supine position, worst case) the first measurement, due to pure random variation. The ICC was > 0.7 for all the parameters (range 0.71 . 0.86). The estimated sample size ranged from 16 . 33 participants. In conclusion, a large random variation (within individuals) of short-term HRV parameters (both the supine and standing position) must be considered when the treatment effects are detected. Despite a low absolute reliability, the random error represents a limited portion of the total measurement variability amongst individuals, which indicates a solid relative reliability. Thus, differences between individuals are primarily caused by the true value of individuals.